Endoscopic submucosal dissection of a giant rectal adenoma manifesting as McKittrick-Wheelock syndrome = Endoskopische Submukosadissektion eines gigantischen Rektumadenoms manifestiert als McKittrick-Wheelock-Syndrom - Kouladouros, Konstantinos; Schneider, Klaus; Kubicka, Stefan; Hörner, Christian; Hirth, Michael (Zeitschrift für Gastroenterologie, 2023)
McKittrick-Wheelock syndrome (MKWS) is an uncommon clinical manifestation of large, villous, epithelial lesions of the distal colon and rectum. Excessive secretion of electrolyte-rich mucus from these lesions leads to secretory diarrhea, electrolyte disorders and acute renal failure. Several cases of MKWS have been reported since its initial description in 1954. The definitive treatment for the great majority of MKWS cases has consisted of surgical resection of the affected part of the colorectum, usually in the form of a low anterior resection or an abdominoperineal resection with the formation of an ostomy. Recent developments in endoscopic resection techniques now offer new, minimally invasive treatment alternatives for MKWS patients. We present the first reported case in the Western world of MKWS caused by a rectal adenoma with a size of 19 × 10 cm, treated through endoscopic submucosal dissection. Through the lessons learned by this case, as well as by a thorough review of the literature, we discuss this uncommon syndrome, focusing on treatment alternatives.
Gesehen am 20.11.2023